Synthesis, Crystal and Supramolecular Structures of Dinuclear Cu(II) Complex Based on 2,3-Dihydroxybenzaldehyde and 3-Ethoxysalicyladehyde - Wang, P.; Zhao, L. (Asian Journal of Chemistry, 2015)
A dinuclear copper(II) complex with a asymmetrical Salamo-type chelating ligand 3-ethoxysalicylaldehyde-O-(2-hydroxyethyl) oxime (H2L2), has been synthesized by the reaction of copper(II) salts with a Salamo-type chelating ligand 6-ethoxy-6'-hydroxy-2,2'-[1,1'-(ethylenedioxy-dinitrilo) dimethylidyne]diphenol (H3L1). Obviously in the process of the reaction, there is a cleavage of N-O bond which give the ligand H2L2. The formula of Cu(II) complex may be suggested as [Cu2(L2)2].